Determining the Predictors of Self-Management Behaviors in Patients With Type 2 Diabetes: An Application of Socio-Ecological Approach - Aghil Habibi Soola; Mahnaz Davari; Hamed Rezakhani Moghaddam (Frontiers Media S.A., 2022)
BackgroundType 2 diabetes complications are responsible for 2% of hospital emergency visits. Self-management practices are one of the most essential approaches to control type 2 diabetes. The goal of this study was to use an ecological approach to investigate the predictors of self-management behaviors in diabetes patients referred to the emergency department in Ardabil in 2020.MethodsIn this cross-sectional study, 273 individuals with type 2 diabetes who were sent to the emergency department of Imam Khomeini Educational and Medical Center in Ardabil were included using the available sample method. Demographic information questionnaires, including the Diabetes Distress Screening Tool (DDS2), General Diabetes Knowledge (DKT2), Diabetes Empowerment Questionnaire (DES-SF), Patient Health Questionnaire 9 (PHQ 9), Beliefs to Treatment Effectiveness Scale (BTES), Diabetes Self-Efficacy Scale (DSES), Chronic Illness Resources Survey (CIRS), Situational Effects Questionnaire, and Diabetes self-management support (DSMS), were all used to collect data. The independent t-test, one-way ANOVA, Pearson correlation coefficient, and multiple regression were used to analyze the data.ResultsThe results of the study showed that in the framework of ecological approach, predictors of self-management behaviors at the four levels are as follows: at the individual level-gender (p = 0.025), education (p = 0.002), duration of diabetes (p = 0.38), having a glucometer at home (p < 0.001), diabetes empowerment (p < 0.001), personal support (p = 0.002), and self-efficacy (p = 0.047); at the interpersonal level-the main health support (p < 0.001), membership in social networks (p < 0.005), family/friends support (p < 0.001), and neighborhoods support (p < 0.001); at the group and organizational level-organizational support (p = 0.013); at the community and policy level-the impact of mass media in health (p < 0.001) and situational influence (p < 0.001).ConclusionThe impact of non-individual levels, such as the environment, on a person's decision to manage diabetes is crucial. Diabetes management necessitates a significant amount of effort, which involves maintaining the health of diabetes patients and the community while also minimizing emergency department workload.